DESIGN A MONITORING AND AUTOMATION SYSTEM FOR DRINKING WATER FILLING WITH VOICE COMMANDS USING GOOGLE ASSISTANT - Manalu, Madoni Eprahim; Saleh, Muhammad; Priyatman, Hendro (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Drinking water filling stations currently still use faucets or buttons to stiffen drinking water filling, where the user is sometimes negligent which results in water overflow during the drinking water filling process and the availability of gallons of water at drinking water filling stations also often runs out. The purpose of this study is to monitor the availability of gallons of water at drinking water filling stations and fill drinking water with voice commands according to the desired water volume using Google Assistant. The command code given is "Turn on the Water Pump", "Turn Off the Water Pump", "Turn on 240 Milliliters", "Turn on 600 Milliliters" and "Turn on 1000 Milliliters" to Google Assistant. The result obtained from this study is the percentage of success of the command code which is 100%. Google Assistant is not able to detect voice commands with environmental conditions of noise interference above 88 dB. The average response speed the tool works at when given a command is 2253 milliseconds. The average error percentage of the HC-SR04 ultrasonic sensor with a manual gauge to determine availability in gallons is 1.8%. The success percentage of the E18-D80NK infrared sensor is 100%. The average error percentage   of the Water Flow Sensor Yf-S201 with a measuring teapot when filling 240 milliliters of drinking water is 8.51%, 600 milliliters is 4.05% and 1000 milliliters is 2.35%.